How schools can aid children’s resilience in disaster settings: The contribution of place attachment, sense of place and social representations theories - Pacheco, Emily-Marie; Parrott, Elinor; Oktari, Rina Suryani; Joffe, Helene (Frontiers in Psychology, 2022)
Disasters incurred by natural hazards affect young people most. Schools play a vital role in safeguarding the wellbeing of their pupils. Consideration of schools' psychosocial influence on children may be vital to resilience-building efforts in disaster-vulnerable settings. This paper presents an evidence-based conceptualization of how schools are psychosocially meaningful for children and youth in disaster settings. Drawing on Social Representations and Place Attachment Theories, we explore the nature of group-based meaning-making practices and the meanings that emerge concerning school environments in disaster settings. We contribute a novel understanding of how schools may mitigate psychosocial risk for young people by considering the function of how schools are conceptualised at four levels: (1) as physical environment, (2) as social arena, (3) as a place with individual and (4) group-based significance. In each of these domains schools can foster disaster resilience in young people. This paper highlights the evidence concerning the functions of schools beyond their capacity as educational institutions, critically considering their social and physical functions in their communities. This evidence can inform stakeholders involved in disaster resilience building.